Lost in translation? How project actors shape REDD+ policy and outcomes in Cambodia. (April 2015) - Pasgaard, Maya
Abstract Forest protection policies to Reduce Emissions from Deforestation and forest Degradation (REDD+) are currently being implemented by international donors, governments and conservation agencies across the developing world aiming for reduction of greenhouse gases while ensuring fair distribution of benefits. This paper draws on a case study in northern Cambodia to analyse how conservation practitioners and the local forest management committees engaged in implementing REDD+ actively translate and influence the policy and its implementation in accordance with their respective interests through particular communication strategies. When assessing project progress and outcomes, the conservation practitioners involved in implementing projects show an interest in emphasising positive project assessments by downplaying potential project complications, and by primarily communicating with pro‐REDD+ members of the local communities. Powerful actors in the local forest management committees adopt the conservation rhetoric of these practitioners; at the same time, they can interpret and control local access to resources to their own advantage. By doing so, they can ensure continued support, while not necessarily representing all community members or sharing benefits equally. The processes and consequences of this policy translation in a REDD+ arena are discussed and compared with existing dominant trends in environment and development policies.